Plant Genetic Resources Information System of Slovakia as the Primary Source of the Information - Mendel, Lubomir; Hauptvogel, Pavol; Čičová, Iveta (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
Thanks to the support of two projects from European Regional Development Fund of European Union the National Agricultural and Food Centre, Research Institute of Plant Production in Piešťany (Slovak Republic) provides the development and deployment of an information system GRISS designed for complex information management research of plant genetic resources for food and agriculture and to support of management processes accessions of plant genetic resources stored in Genebank according to international principles and in accordance with the National Programme of Conservation of Plant Genetic Resources for Food and Agriculture in Slovak Republic. Genebank is responsible for the providing of the Genetic Resources Information System of Slovakia (GRISS). An information system is used through the Web interface used by the curators of collections of plant genetic resources and users from breeder’s institutions, universities, public institutions, and others. Currently, the Information System provides passport information on more than 27.000 accessions and more than 23.000 accessions stored in active and basic collection in the Genebank. At present, the Slovakian collection in the European Search Catalogue for Plant Genetic Resources (EURISCO) represents 17.142 accessions from which 640 accessions are included in the European Genebank Integrated System (AEGIS). On request of plant breeders, researchers, but also private persons, the genebank is distributing research material amounting to over 2.000 samples in response to more than 50 individual requests per year. The information system GRISS is freely accessible at http://griss.vurv.sk.